Management of Kidney Transplant Outpatients With COVID-19: A Single Center Experience - Matysková Kubišová, Michaela; Dusilová Sulková, Sylvie; Moučka, Petr; Pokorná, Anita; Heislerová, Marcela; Guňka, Igor; Navrátil, Pavel; Pacovský, Jaroslav; Malá, Alena; Šafránek, Roman (Transplant international, 2024)
Patients undergoing kidney transplant are at risk of severe COVID-19. Our single-center retrospective analysis evaluated the outcomes of kidney transplant outpatients with COVID-19 who were managed with reduced immunosuppression and treatment with molnupiravir. Between January 2022 and May 2023, we included 93 patients (62 men, average age 56 years), serum creatinine 127 (101-153) μmol/L. Molnupiravir was administered, and immunosuppressive therapy was reduced immediately following the confirmation of SARS-CoV-2 infection by PCR, which was 2 (1-3) days after the onset of symptoms. Only three (3.2%) patients required hospitalization, and one patient died. Acute kidney injury was observed in two patients. During the follow-up period of 19 (15-22) months, there was no significant increase in proteinuria, no acute or new chronic graft rejection, and kidney graft function remained stable; serum creatinine was 124 (106-159) μmol/L post-COVID-19 infection and 128 (101-161) μmol/L at the end of the follow-up period. Our results demonstrate that early initiation of molnupiravir treatment combined with a temporary reduction in immunosuppressive therapy results in favorable clinical outcomes in patients with COVID-19, with preservation of good graft function and no episodes of graft rejection.
Keywords: dospělí; Antiviral Agents; COVID-19; Kidney Transplantation; imunosupresiva; retrospektivní studie; Humans; Creatinine; lidé středního věku; Middle Aged; Outpatients; transplantace ledvin; mužské pohlaví; Adult; antivirové látky; výsledek terapie; Treatment Outcome; ženské pohlaví; rejekce štěpu; Immunosuppressive Agents; pacienti ambulantní; lidé; SARS-CoV-2; kreatinin; Graft Rejection; Aged; senioři; Male; Retrospective Studies; Female